2014
DOI: 10.1007/s13340-014-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of slowly progressive type 1 (insulin-dependent) diabetes mellitus: a comparative study based on degree of obesity at diagnosis of diabetes

Abstract: Objective For early differential diagnosis of slowly progressive type 1 diabetes mellitus (SPIDDM) from type 2 diabetes mellitus, we investigated clinical history and characteristics of patients with SPIDDM with or without obesity. Research design and methods Subjects were 39 patients (20 men and 19 women) diagnosed with SPIDDM based on positive antibodies against glutamic acid decarboxylase (GAD) and/or islet-associated antigen 2 (IA-2), with more than 3 months from diabetes mellitus (DM) diagnosis to initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…On the other hand, patients with LADA or SPT1D who have a lower GADA titer or a smaller number of other islet-related autoantibodies may have a slower decline in endogenous insulin secretion (9,11,12,27), whereas the presence of IAA is a predictor of a rapid decrease in endogenous insulin secretion (15). In the present case, our non-obese GADA-negative patient with single IAA positivity exhibited a short duration from the onset of diabetes mellitus to the initiation of insulin therapy, which was similar to the course of previously reported non-obese Japanese patients with GADA-positive SPT1D (26), and she experienced progression to almost complete insulin deficiency within 2 years after the onset of diabetes mellitus (Table 2B).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, patients with LADA or SPT1D who have a lower GADA titer or a smaller number of other islet-related autoantibodies may have a slower decline in endogenous insulin secretion (9,11,12,27), whereas the presence of IAA is a predictor of a rapid decrease in endogenous insulin secretion (15). In the present case, our non-obese GADA-negative patient with single IAA positivity exhibited a short duration from the onset of diabetes mellitus to the initiation of insulin therapy, which was similar to the course of previously reported non-obese Japanese patients with GADA-positive SPT1D (26), and she experienced progression to almost complete insulin deficiency within 2 years after the onset of diabetes mellitus (Table 2B).…”
Section: Discussionsupporting
confidence: 89%
“…Studies of GADA-positive LADA have revealed that the endogenous insulin secretion in non-obese patients tends to decrease more quickly than that in obese patients (9). A study of GADA-positive Japanese patients with SPT1D also revealed that non-obese patients are likely to exhibit greater decreases in endogenous insulin secretion in comparison to obese patients; they are also likely to have a shorter period between the onset of diabetes mellitus and the initiation of insulin therapy, with a median period of approximately 1.5 years (26). On the other hand, patients with LADA or SPT1D who have a lower GADA titer or a smaller number of other islet-related autoantibodies may have a slower decline in endogenous insulin secretion (9,11,12,27), whereas the presence of IAA is a predictor of a rapid decrease in endogenous insulin secretion (15).…”
Section: Discussionmentioning
confidence: 99%
“…SPT1D is characterized by a gradual decrease in endogenous insulin secretion, the presence of islet autoantibodies, the absence of DKA at diabetes onset, and clinical features similar to those of T2D. The rate of decrease in insulin secretion varies from case to case, and many patients progress to insulin deficiency within 6 years after diabetes onset (20); however, some patients do not exhibit insulin deficiency even more than 10 years after DM onset because of extremely gradual or no decrease in insulin secretion capacity (22). Most SPT1 D cases are GADA-positive, but GADA-negative/IA-2Abpositive patients have been reported (23,24); these patients tended to exhibit better-preserved insulin secretion than did GADA-positive patients.…”
Section: Discussionmentioning
confidence: 99%